Synthesis, Antimicrobial Evaluations, and DNA Photo Cleavage Studies of New Bispyranopyrazoles. (30th September 2015) - Yusuf, Mohamad; Kaur, Manvinder; Sohal, Harvinder Singh
Abstract : The bispyranopyrazoles (4a, 4b, 4c, 4d, 4e, 4f, 4g ) were synthesized from the reactions of dibenzaldehydes (2a, 2b, 2c, 2d, 2e, 2f, 2g ) with 3‐methylpyrazole‐5‐one3 and malononitrile by refluxing under alcoholic medium. The dibenzaldehydes were obtained from theO‐alkylation of 3‐hydroxybenzaldehyde with suitable 1, ω‐dibromoalkanes under the alkaline conditions in the presence of dry EtOH/DMF. The structures of bisheterocyclics were determined from rigorous analysis of their spectral parameters (IR, 1 H‐NMR, 13 C‐NMR, and ESI‐MS). The newly prepared compounds were screened for theirantimicrobial activity against seven bacterial and five fungal strains. The DNA photo cleavage potential of these compounds was also evaluated by using agarose gel electrophoresis, and bispyranopyrazoles4b, 4d and4e exhibited significant level of DNA photocleavage activity. Abstract :